ANALYSIS OF THE IMPLEMENTATION OF THE MERDEKA CURRICULUM IN THE SUBJECT OF ISLAMIC RELIGIOUS EDUCATION CLASS X AT THE NUSANTARA ISLAMIC HIGH SCHOOL - Annisyah, Sunanul (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
The research objective is to describe the application of the Merdeka curriculum to Islamic religious education subjects at the Nusantara Islamic High School. The research uses a qualitative descriptive method with a phenomenological approach. The research results show that Islamic Religious Education teachers apply Problem-Based Learning strategies and use Audio-Visual learning media. As for learning evaluation, the teacher gives assignments, tests, and remedial. The obstacles to implementing the Merdeka curriculum are that teachers find it difficult to create lesson plans in determining the learning media to be used, there is no update on the use of learning strategies and media and it is difficult to access the internet. Efforts to implement an independent teacher curriculum use aspects of assessing attendance, skills, and activeness. Teachers are also given training in implementing the Merdeka curriculum. The impact of implementing the Merdeka curriculum on Islamic religious learning at Nusantara Islamic High School is that it is easier for students to understand PAI material and students become more active in learning.